Exploring the Relations between Student Cynicism and Student Burnout. Issue 1 (August 2015) - Wei, Xueyan; Wang, Rongrong; MacDonald, Elizabeth
Research on the negative effects of student cynicism has been limited, especially regarding its relation to student burnout. This study examined the relations among student cynicism (policy cynicism, academic cynicism, social cynicism, and institutional cynicism) and student burnout, as evidenced by emotional exhaustion, depersonalization, and reduced personal accomplishment, in a sample of 276 Chinese undergraduates. Hierarchical multiple regressions showed that four aspects of student cynicism together explained substantial variance in student burnout. Policy cynicism was the strongest contributor to emotional exhaustion. Social cynicism was the primary contributor to depersonalization, and also to reduced personal accomplishment. Student cynicism overall had the strongest relationship with reduced sense of personal achievement. The findings outline the negative functional relations between student cynicism and student burnout.